Electroacupuncture superiority in knee osteoarthritis: a meta-analysis of four acupuncture techniques - Chen, Yu; Xing, Chunyan; Wan, Qi; Guo, Gengchun; Li, Wanlang (Frontiers in Medicine, 2025)
BackgroundKnee osteoarthritis is the most prevalent chronic joint disease affecting persons >50 years, which significantly impairs the patients’ lives. Although acupuncture can treat knee osteoarthritis; none of the studies have compared the effectiveness of four common acupuncture techniques (electroacupuncture, filiform acupuncture, warming acupuncture, and fire acupuncture) in knee osteoarthritis.MethodsThe Web of Science, EMBASE, PubMed, Scopus, and CNKI databases were searched for the clinical randomized controlled trials of electroacupuncture, filiform acupuncture, warming acupuncture, and fire acupuncture in the treatment of knee osteoarthritis published before September 1, 2024. We collected 52 studies and used R software to analyze data.ResultsThe results of meta-analysis showed that the efficacy rates for electroacupuncture, filiform acupuncture, warming acupuncture, and fire acupuncture were 91.5, 83.4, 84.9, and 83.5%, respectively. The respective visual analog scale (VAS) scores were 2.1, 3.2, 2.9, and 4.1, respectively. Moreover, the patient’s age and body mass index (BMI) can negatively affect the efficacy rate of acupuncture therapies, whereas age and BMI positively impacts the VAS scores.ConclusionThus, our study suggests that electroacupuncture has the best clinical efficacy for knee osteoarthritis; however, patients’ age and BMI should be considered in future acupuncture therapies.